2019
DOI: 10.3390/cancers11091289
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA Replication Stress and DNA Double-Strand Break Repair for Optimizing SCLC Treatment

Abstract: Small cell lung cancer (SCLC), accounting for about 15% of all cases of lung cancer worldwide, is the most lethal form of lung cancer. Despite an initially high response rate of SCLC to standard treatment, almost all patients are invariably relapsed within one year. Effective therapeutic strategies are urgently needed to improve clinical outcomes. Replication stress is a hallmark of SCLC due to several intrinsic factors. As a consequence, constitutive activation of the replication stress response (RSR) pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…Also, c-MYC and MYCN amplification is a predictive biomarker for PARP inhibitor sensitivity in glioblastoma ( 53 ). Most importantly, we and others recently demonstrated that inhibiting RSR pathway is effective in treatment of SCLC ( 54 , 55 ). Together, these studies demonstrated that targeting one or more DDR proteins is a desirable strategy for the treatment of a subset of SCLC.…”
Section: Discussionmentioning
confidence: 86%
“…Also, c-MYC and MYCN amplification is a predictive biomarker for PARP inhibitor sensitivity in glioblastoma ( 53 ). Most importantly, we and others recently demonstrated that inhibiting RSR pathway is effective in treatment of SCLC ( 54 , 55 ). Together, these studies demonstrated that targeting one or more DDR proteins is a desirable strategy for the treatment of a subset of SCLC.…”
Section: Discussionmentioning
confidence: 86%
“…These might be considered as SCLC’s weak spots. After providing a short review on the principles of RS, Bian et al [ 16 ] summarize the source of RS in SCLC and review the strategies to take advantage of this by either increasing the RS or blocking the DDR system in the tumor cells. Of several inhibitors that target the replication stress pathway, PARP1 and WEE1 appear to be the most promising, based both on preclinical and clinical studies.…”
Section: Targeting Replication Stressmentioning
confidence: 99%
“…The binding of WEE1 kinases to 14-3-3 protein, which activates WEE1 kinases, may be carried out in two different ways-via the phosphorylation of ser642 (with participation of CHK1) or autophosphorylation. WEE1 inhibitor abrogates the G2/M checkpoint, resulting in cancer cell death coated ssDNA adjacent to the double-stranded DNA (dsDNA) act as a platform to trigger the ATR/CHK1 [35]. ATR combines with ATR-interacting protein (ATRIP), and their complexes are located in the cell nucleus at the sites of DNA damage [36].…”
Section: Replication Stress and Cell Cycle Disturbances In Ovarian Cancermentioning
confidence: 99%